Effect of Antioxidant Therapy on Oxidative Stress in Vivo - Anna Maria Fratta Pasini; Luciano Cominacini (MDPI AG, 2021)
Over the last few decades, many efforts have been put into fields that explore the potential benefits of antioxidants, especially with regards to aging, cancer, cardiovascular diseases, and neurodegenerative diseases [...]